2022
DOI: 10.22146/ijc.70799
|View full text |Cite
|
Sign up to set email alerts
|

A New Flow Injection System with Merging-Zone Technique for the Determination of Copper(II) by Neocuproine Reagent in Aqueous Solution

Abstract: A fast, simple, and high throughput sample merging-zone flow injection design was developed to determine copper(II) in aqueous solution. The procedure is based on the reduction of copper(II) to copper(I) by uric acid followed by a direct reaction with Neocuproine reagent (NC). The orange-yellow complex that forms absorb light at 454 nm. All conditions of the new flow injection unit were investigated. The analytical curve of copper(II) was linear with (r2) value of 0.9978, in the range of 0.4 to 40 mg/L with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Obviously, these LoDs are lower than this work (9 mg L -1 ) since our linear range was 34 -2000 mg•L -1 . In fact, a comparison with the literature supports this, revealing a three-orderof-magnitude difference between the LoD and the maximum concentration of the linear range in our study and the referenced works [52][53][54][55][56][57][58][59]. As regards selectivity, another parameter to compare, the previously mentioned studies showed good selectivity for determining Cu(II) [52][53][54][55][56][57][58][59].…”
Section: Parametersupporting
confidence: 86%
See 3 more Smart Citations
“…Obviously, these LoDs are lower than this work (9 mg L -1 ) since our linear range was 34 -2000 mg•L -1 . In fact, a comparison with the literature supports this, revealing a three-orderof-magnitude difference between the LoD and the maximum concentration of the linear range in our study and the referenced works [52][53][54][55][56][57][58][59]. As regards selectivity, another parameter to compare, the previously mentioned studies showed good selectivity for determining Cu(II) [52][53][54][55][56][57][58][59].…”
Section: Parametersupporting
confidence: 86%
“…Value Sensitivity (V L mg -1 ) 0.00078 ± 0.00002 Detection limit (mg L -1 ) 9 Quantification limit (mg L -1 ) 34 Linear range (mg L -1 ) 34 -2000 Repeatability (CV) (n=6) 0.3% -1.1% Reproducibility (CV) (n=12) 3.9% -7.4% Selectivity not interferences [52] Sample throughput (h -1 ) 7…”
Section: Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its selectivity for copper(I) and potent visual absorbance of the Cu(DMP) 2+ adduct, 2,9-dimethyl-1,10-phenanthroline (NC) is typically the reagent chosen for the colorimetric measurement of copper(I) (14) Water-insoluble mefenamic acid is somewhat soluble in (chloroform) and (ethers), faintly soluble in ethanol (4.6 mg/mL) and water (1:9), and more soluble in dimethylformamidee (38.5 mg/mL) (4) Mefenamic acid reduces inflammation and pain by inhibiting COX and prostaglandin synthesis since it provides cerebral and peripheral analgesia. Its nonselective COX inhibitors inhibit both COX-1 and COX-2 enzymes (5) Mefenamic Acid (MFA) operates in the same way as other nonsteroidal anti-inflammatory medicines by which blocking the enzymatic prostaglandin synthase (6) There are several known and reported analytical methods for measuring MEF acid in biological and pharmacological products (7) Spectrophotometry (8) Gas Chromatography (9) Extraction method of Micro-electrodriven Membranes in 2 Phases (10) capillary electrophoresis with two channels (11) RP-HPLC (12) Fluorometric method (13) Hyphenated Tech-niques (14) Electrospray Ionization Mass Spectrometry (15) Turbidity Measurement (16) flow injection method (17) MEF is determined by different flow injection technique, it has been estimated in pharmaceuticals by flow-injection (18) and estimation of Mefenamic Acid in Aqueous Solutions Using Reverse -Continuous Flow Injection Analysis (6) determination of MEF in pharmaceuticals formulation by flow-injection Fluorometry (21). However, in recent years there has been a growing interest in the use of Neocuproine (2,9-dimethyl-1,10-phenanthroline) as a complexing agent in analytical chemistry.…”
Section: Highlight Introductionmentioning
confidence: 99%